2007
DOI: 10.1093/ee/36.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Behavioral Constraints on the Infection of Wireworms by Metarhizium anisopliae

Abstract: Environmental and behavioral factors that affect the infection of wireworms [Agriotes obscurus L. (Coleoptera: Elateridae)] by a unique isolate of Metarhizium anisopliae Sorokin (Hypocreales: Clavicipitaceae) were studied. After wireworms were placed in soil containing 10(6) M. anisopliae conidia/g and incubated at 6, 12, or 18 degrees C, significant disease development and wireworm mortality occurred only in those wireworms incubated at 18 degrees C. At this temperature, mortality was found to be dependant on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…The genus Metarhizium contains biologically distinct subtypes with wide insect host ranges, e.g., Metarhizium robertsii [formerly known as Metarhizium ani- abilities to form associations with different plant species (Bidochka et al, 2001;Fisher et al, 2010). Overall, the effects of Metarhizium on plants are favorable as application of conidia to corn seeds significantly increased yields (Kabaluk and Ericsson, 2007), and the fertility of soils treated with some Metarhizium strains can be improved beyond insect control (unpublished data), but there is very little data as to the ecological consequences of these interactions. The fact that many genotypes of Metarhizium appear to be specialized to different plants (Fisher et al, 2010), suggests that the impact of rhizosphere competence by Metarhizium on plant ecology in general could be considerable with implicit co-evolutionary implications.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Metarhizium contains biologically distinct subtypes with wide insect host ranges, e.g., Metarhizium robertsii [formerly known as Metarhizium ani- abilities to form associations with different plant species (Bidochka et al, 2001;Fisher et al, 2010). Overall, the effects of Metarhizium on plants are favorable as application of conidia to corn seeds significantly increased yields (Kabaluk and Ericsson, 2007), and the fertility of soils treated with some Metarhizium strains can be improved beyond insect control (unpublished data), but there is very little data as to the ecological consequences of these interactions. The fact that many genotypes of Metarhizium appear to be specialized to different plants (Fisher et al, 2010), suggests that the impact of rhizosphere competence by Metarhizium on plant ecology in general could be considerable with implicit co-evolutionary implications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that lower temperatures slow down fungal infections of wireworms (Kabaluk and Ericsson 2007). Accordingly, an EPF application during summertime in the northern hemisphere, as performed in our experiment, should promote fungal growth and efficacy.…”
Section: Treatmentmentioning
confidence: 66%
“…This stimulated research aimed at the development of ecologically acceptable control methods (Ester and Huiting 2007;Kabaluk et al 2005;Kleespies et al 2013;Kölliker et al 2011;Ladurner et al 2009). Among the natural enemies of wireworms, entomopathogenic fungi (EPF), especially those in the genus Metarhizium Sorokin (Hypocreales: Clavicipitaceae), are currently regarded as the most promising for wireworm control (Ansari et al 2009;Eckard et al 2014;Kabaluk 2007;Kabaluk and Ericsson 2007;Kölliker et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…There was neither correlation between soil type and efficiency nor between soil type and conidial viabilities. Similarly, Kabaluk et al (2007) observed that efficacy of M. anisopliae for wireworms differed significantly among sand, clay, and organic soils at the same moisture level. In another study, B. bassiana killed more ants in silt (70:15:15, silt: sand:clay) and in sandy soil (15:70:15) than in clay (15:15:70, as in the control) (Fuxa et al, 2004).…”
Section: Factors Affecting Fungi Used As Mpcas In Soilmentioning
confidence: 75%